Assessment of solar photo-Fenton in raceway pond reactors for micropollutant removal in secondary effluents from agro-food industry and municipal WWTPs Evaluación del proceso foto-Fenton solar en reactores tipo raceway para la eliminación de microcontaminantes en efluentes secundarios de EDAR municipales y de la industria agro-alimentaria - Rivas Ibáñez, Gracia (Tesis Doctorales (Edición Electrónica), 2017)
There is increasing environmental concern about the presence of organic micropollutants in aquatic systems. One of the main factors behind their release into the environment is the poor efficiency of their degradation in conventional wastewater treatment plants, commonly based on biological processes. As such, it involves the continuous release into the water cycle of substances which have been recognised as a potential hazard to the environment and human health even when detected at very low concentrations. To overcome this problem, research is being carried out to remove them by including a tertiary stage in wastewater treatment plants. In this regard, advanced oxidation processes have been widely used due to the generation of highly reactive hydroxyl radicals, which help to oxidise organic compounds. Amongst them, the photo-Fenton process has proven to be effective in micropollutant removal. However, more research is still needed for their application in wastewater treatment plants at real scale. This study was designed to assess different operating strategies of the photo-Fenton process as tertiary treatment to remove micropollutants in secondary effluents from the agro-food industry ("Cítricos del Andarax S.A.", Almería, Spain) and municipal wastewater treatment plants. The evaluation was based on the characteristics of the water matrix to be studied, and the feasibility to scale up the process to a realistic levels applying the recently proposed low-cost photoreactor: the raceway pond reactor (RPR). It is extensive non-concentrating photoreactor which allows large volumes of water to be treated and consists of channels where water is set in motion by a paddlewheel system. In summary, the work presented in this Ph.D. thesis showed that controlling pH in the biological depuration of agro-food industry wastewater enables micropollutant removal by the photo-Fenton process and reduces reactant cost. Additionally, the excess sludge generated during the biological treatment can be reduced by ultrasonication of the purged sludge, which degrades most of the pesticides absorbed in the sludge. Raceway Pond Reactors allow a high treatment capacity for micropollutant removal by solar driven Fenton processes such as the sequential iron dosage and using the Fe3+/EDDS complex. They have proved to be efficient treatments for micropollutant and toxicity removal in WWTP secondary effluents.